Prediksi Harga Saham PT. Unilever Indonesia TBK Dengan Metode Regresi Linier Sederhana - Wilda, Robiatul Witari; Sukmarini, Mita Akbar; Mahar, Alicia Christina (Universitas Palangka Raya, 2024)
The world of investment is a dynamic market characterized by its fluctuations, including changes in stock values. This research is motivated by the need to predict stock prices with high accuracy to support more precise investment decision-making. PT. Unilever Indonesia Tbk is one of the leading companies in Indonesia, and thus, forecasting its stock prices holds strategic value for investors. However, predicting stock prices is a complex task influenced by various economic and company-specific factors. This study aims to analyze the effectiveness of the simple linear regression method in forecasting the stock prices of PT. Unilever Indonesia Tbk. The results show that this method can produce accurate predictions, with a forecasted value of Rp 2,707 and a Mean Absolute Percentage Error (MAPE) of 2.65%. The application of this method has significant contributions in the investment world, where accurate stock price predictions can assist investors in determining the optimal timing for investment transactions.